Barriers and enablers to source plasma donation by gay, bisexual and other men who have sex with men under revised eligibility criteria: protocol for a multiple stakeholder feasibility study - Vesnaver, Elisabeth; Goldman, Mindy; O’Brien, Sheila; MacPherson, Paul; Butler-Foster, Terrie; Lapierre, Don; Otis, Joanne; Devine, Dana V; Germain, Marc; Rosser, Andrew; MacDonagh, Richard; Randall, Taylor; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Blood donation policy in Canada for gay, bisexual and other men who have had sex with men (gbMSM) has changed progressively in the last decade from indefinite deferral to 3-month deferral from last male-to-male sex. Driven by safety data and overseen by the national regulator, more inclusive policies continue to redress the disparity in donation for gbMSM. At the same time, the need for source plasma to prepare fractionated blood products is growing worldwide. The collection and processing of source plasma ensures greater safety compared to whole blood donation with respect to transfusion-transmitted infection. This greater safety offers an opportunity to evolve policies for gbMSM from time-based to behaviour-based deferral using revised eligibility criteria. However, changing policies does not in itself necessarily guarantee that gbMSM will donate or that staff in donor clinics are ready to support them to do so. In anticipation of a move to behaviour-based donation screening for gbMSM in Canada, we aim to assess the acceptability of and perceived barriers and enablers to source plasma donation using revised screening criteria for gbMSM among key stakeholders to inform policy implementation strategies. Methods This mixed-methods feasibility study will involve gbMSM and donor centre staff to understand modifiable barriers to implementing more inclusive eligibility criteria. Key informant interviews and surveys will be rooted in the Theoretical Domains Framework to identify modifiable factors associated with source plasma donation motives in gbMSM and training needs in donation centre staff. We will use an integrated knowledge translation approach involving a partnership between researchers, the national blood operator and gbMSM, situating knowledge users as key research team members to ensure their perspectives inform all aspects of the research. Discussion Our integrated knowledge translation approach will provide a more comprehensive and collaborative understanding of blood operator and gbMSM needs while accelerating the implementation of study findings. Given the historical backdrop of the decades of exclusion of sexually active gbMSM from blood donation, this study has the potential not only to inform a process and policy for gbMSM to donate source plasma, a blood product, but also offers opportunities for new relationships between these knowledge users.